Правовий статус органів місцевої влади у Західній Україні у складі Польської держави (1921-1939 рр.) - Олійник, Ю.; Olijnyk, Yu. (Волин. нац. ун-т ім. Лесі Українки, 2018)
У статті проаналізовано правовий статус органів місцевої влади в Західній Україні у складі Польської держави (1921-1939 рр.). Значну увагу зосереджено на характеристиці польських конституцій 1921 і 1935 рр., що визначали характерні риси організації органів місцевої влади в Західній Україні. Їх правовий статус характеризувався низкою особливостей, причини яких полягали з одного боку в дискримінаційній політиці польської влади щодо українців, з іншого – у етнічних та соціально-економічних потребах українського населення. Головною метою такого законодавчого регулювання була асиміляція українських територій, полонізація українців як однієї з найбільших національних меншин. The article analyzes the legal status of the local authorities in Western Ukraine, when it was a part of the Polish state (1921-1939). After the collapse of the Russian and Austro-Hungarian Empires and the end of the First World War, Ukraine failed to complete the unification of all its lands. The Ukrainian people, being disorganized and due to the unjust policy of the governments of the Entente and Russia, had not gained the desired freedom and state independence. The Ukrainian Galicia was forcibly annexed by Poland after the defeat in the Polish-Ukrainian war of 1918-1919 and in accordance with the Riga Treaty of 1921, signed by the RSFSR, the USSR and Poland. The Western Volynian districts, formerly part of the Czarist Russia, were also forcibly annexed by the Polish state. These lands received the name of Western Ukraine in the historical literature. The author lays emphasis on the in-depth analysis of the Polish constitutions of 1921 and 1935 and reveals the characteristic features of the local governmental organization and their functioning in Western Ukraine (1921-1939).
Legal Status of the Local Authorities in Western Ukraine as Part of the Polish State (1921-1939)
Keywords: правовий статус; місцева влада; компетенція; Західна Україна; Польща.; legal status; local authorities; competence; Western Ukraine; Poland